(untitled) (International Journal of Occupational Safety and Health, 2026)
This paper is a narrative review on microplastics (MPs). The properties and behavior of MPs in the environment are emphasized, noting that they are groundwater pollutants, are harmful to biotic and abiotic environments, exhibit stable and unique chemical properties, and persist in the environment for prolonged periods. They are resistant to biodegradation, precipitate and accumulate in the bodies of microorganisms. The routes of exposure to MPs in work environments are highlighted, noting that deposition is the main route of human exposure to MPs. The risk assessment for MPs is implemented with the polymer hazard index ecological hazard index, the hazard quotient, and the ecological hazard quotient. The pollution load index, which is related to the microplastic concentration coefficient, and the MPs pollution risk index are utilized. The effects of MPs on humans are highlighted, the main ones being thyroid disorders, headaches, cardiovascular problems and obesity. The prevention and control of MPs pollution is mentioned through the Operation Clean Sweep program, which includes containment measures and employee awareness training. The new contributions of my narrative review are mentioned, which lie in strengthening research on the mechanisms of interactions of MPs with human health and the complete clarification of the organs in which inhaled particles are deposited. Another contribution is the elimination of biochar limitations such as the quantification of the dynamic accumulation of MPs in the environment.